Educação digital, educação desigual: a influência do neoliberalismo na glocalização da educação brasileira em contexto pandêmico - Frigo, Letícia Ferreira (2023)
This study aims to analyze the meanderings through which dromoaptitude has settled in teaching practices, becoming an exclusive means of education throughout the pandemic period. The research problem alludes to the imposition of a real-time education pattern, mediated by sophisticated devices, instantly put into practice to all teachers, thus, in the COVID-19 pandemic context, becoming the solution for the education in the São Paulo state. The hypotheses to be studied investigate how the use of technologies has become indispensable in the quality education discourse, becoming a desired differential. The process of dromoaptitude in teachers was accelerated and massified by the Covid-19 pandemic and therefore, so was the precariousness process of teaching. This study intends to justify how neoliberal measures are linked to dromoaptitude, and how they were imposed on teachers during the pandemic as an educational solution, bringing a whole new array of demands to the teachers along with the new responsibilities of developing new digital and pedagogical skills. This range of new knowledges and practices, indispensable, invisible and unpaid, corroborate for the dromoaptitude to become inseparable and growing within teaching profession. The research corpus consists on the reading and analysis of the legislation that regulates the national education as of the transformations that descend from these laws, and how such measures impose dromoaptitude on teachers. The methodology developed in this research will be based on reading and analysis of the bibliographical research on the themes proposed by the research problems aiming to meet the research objectives. For the theoretical foundation, this study will be based as a bibliography on the following: to comprehend the Brazilian legislation on education, Mônica Ribeiro da Silva, Carlos Roberto Jamil Cury, Magali Reis and Teodoro Adriano Costa Zanardi, Paulo Freire, Anísio Teixeira, Demerval Saviani, Pierre Bourdieu and John Dewey. To assess the presence of neoliberal ideas in Brazilian education, Wendy Brown, Christian Laval, Pierre Dardot, Milton Santos, Michel Apple, Paula Sibilia, Luiz Carlos de Freitas, Ericka Moreira Martins, Pablo Gentili, Tomaz Tadeu da Silva. To analyze the trajectory of national education since the 1990, Carolina Dalenogare Vaz. To understand glocal and dromoaptitude, research will use Eugênio Trivinho, Paul Virilio, Ciro Marcondes, Filho, Michele Prazeres, Byung-Chul Han, Sérgio Lessa, Joyce Souza, Rodolfo Avelino, Sérgio Amadeu da Silveira, David Harvey, Michel Foucault, Manuel Castells and Shoshana Zuboff